Paradigms of Scientific Integration in Sumatra's State Islamic Universities - Anhar Anhar; Zainal Efendi Hasibuan; Muhammad Darwis Dasopang; Erawadi Erawadi; Magdalena Magdalena; Fakhruddin Fakhruddin; Suwardi Suwardi (Jurnal Ilmiah Peuradeun, 2026)
This article examines the paradigm of scientific integration in Islamic religious universities in Sumatra through a comparative and contextual approach. Although studies on scientific integration have grown rapidly, most remain confined to normative discussions and have not sufficiently examined how integration is constructed, interpreted, and implemented within diverse institutional contexts. Using a quasi-qualitative approach based on in-depth interviews, academic observations, document analysis, and focus group discussions (FGDs), this study explores the dynamics of scientific integration in three State Islamic Universities: UIN North Sumatra, UIN Ar-Raniry Banda Aceh, and UIN Raden Fatah Palembang. The findings show that scientific integration is not understood as a singular unification of religious and scientific disciplines, but as a multi-layered epistemological process encompassing philosophical orientations, methodological alignments, and academic practices. Variations in integration paradigms emerge according to each institution’s vision, historical trajectory, and academic strategy, shaping different models of curriculum design, research orientation, and academic culture. These results indicate that the paradigm of scientific integration in Sumatra develops in a dynamic and context-dependent pattern rather than as a standardized institutional model. Beyond the local context, this study offers a reflective analytical framework for understanding scientific integration as a living epistemological process, contributing to broader discussions on Islamic higher education and contemporary global epistemological challenges.